STRUKTUR DAN FUNGSI SOSIAL KEPERCAYAAN RAKYAT UNGKAPAN LARANGAN MENGENAI MATA PENCAHARIAN DAN HUBUNGAN SOSIAL KELURAHAN BUNGUS TIMUR KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Hairunnisa, Hairunnisa; Nurizzati, Nurizzati; Nst, Muhammad Ismail; Nst., Muhammad Ismail (Universitas Negeri Padang, 2018)
The purposes of this study to describe the value contained in the trust of the people expression prohibition on the village Bungus eastern sub district Bungus Teluk Kabung Padang city. Confidence in the prohibition of prohibition is divided into two categories namely, the expression of the prohibition on livelihood and social relations. This type of research is qualitative research with descriptive method. Research that is first, the structure of prohibited expression about livelihood and social relation of society vilage Bungus Teluk Kabung Padang city. The structure of the prohibed expression is devided into two parts a structure and three parts a structure. Bacakak laki bini ndak buliah, beko habis padi jo ciliang. Quarell husband and wife should not be a result of pigs being consumed by rice. It is seen that the cause bacakak laki bini ndak buliah and that is the result , beko habih padi jo ciliang. A function taht is found in this research, which is to reinforce the religious emotions, and the beliefs of imaginary, educational, and prohibited projection systems. Makan barimah ndak buliah, beko habih padi wak dek mancik. Eat scattered should not, later rice out by rice. The structure of this expression is inculed in the educational function. Eating scattered is not allowed because it does not reflect cleanliness.Keywords : The prohibition expression, livelihood,Â and relation social